Communication skills training: what the vet schools are doing. (31st January 2015) - Mossop, L.; Gray, C.; Blaxter, A.; Gardiner, A.; MacEachern, K.; Watson, P.; Whittlestone, K.; Robbé, I.
Abstract : Increasing emphasis is being placed on communication skills training in UK veterinary curricula, with changes and advances in teaching approaches and the assessment of skills. Here, Liz Mossop and colleagues describe how the different UK schools approach communication skills training and assessment, and consider how this teaching will continue to evolve to meet the needs of the profession and ensure students graduate 'fit to practise' in an ever more demanding environment.